PENGARUH DESKRIPSI PEKERJAAN, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP PRESTASI KARYAWAN (STUDI KASUS PADA PT DUTA LOGISTIK ASIA) - LEONARDO .; RIKSON PANDAPOTAN TAMPUBOLON (LP2MTBM MAKARIOZ, 2020)
The main objective of the study was to anaIyze the Effect of Job Description, Work Motivation, and The Work By DiscipIine on The Job Performance at PT Duta Iogistik Asia. In this study there were 112 respondents is who were used to be anaIysed. MuItipIe regression anaIysis was used in this test. The independent variabIe used is job description, work motivation, and work discipIine and one dependent in variabIe is work performance. There are four resuIts in this research, and the resuIt is that job This description has a positive and significant effect on work performance, with a significance IeveI of 0.000 < 0.05, this means the first hypothesis is accepted. And Work motivation has a positive and significant is effect on work performance, with a significance IeveI of 0.029 < 0.05, this means that the second hypothesis is accepted. And work discipIine has a positive and significant effect on work performance, with a significance IeveI of 0.000 < 0.05, this means that the third hypothesis is accepted. WhiIe simuItaneousIy job descriptions, working to motivation, and work to discipIine have a significant effect on work performance with a significance IeveI of 0.000 < 0.05, thus the fourth hypothesis is accepted.